Prediction Of Solubility Of Solid N-Paraffins In Supercritical Fluids Using Modified Redlich-Kwong Equation Of State - Ratnawati Ratnawati (Dept. of Chemical Engineering, Diponegoro University, 2004)
Three equation of state are used to predict solubilities of solid n-pafaffins in supercritical fluids. The equations are the Redlich-Kwong, the Soave-Redlich-Kwong, and equation proposed by Hartono et.al. (2003; 2004). Both the last two equations were formed by modificating the Redlich-Kwong equqtion of state. With the binary interactions parameter, kif , equals zero, the equations proposed by Hartono et.al. is better than both the Redlich-Kwong and the Soave-Redlich-Kwong equations of state are. Upon optimization with kif as the adjustable parameter, the equation of state proposed by Hartono et.al. is closer to the experimental data than the other equqtions are. For 142 data points of 12 systems the equation proposed by Hartono et. Al. gives the average deviation of 36.6%, while the Redlich-Kwong and the Soave-Redlich-Kwong give 66.7% and 65.8%, respectively.Keywords : equation of state, solubility, supercritical